Perencanaan Biaya Tahun 2025 pada Kegiatan Reklamasi di Banko Barat PT Bukit Asam Tbk Tanjung Enim Sumatera Selatan - Gumanti, Suhardiman; Aisyah Ramadhani, Sisil; Firmansyah, Denny (Journal of Comprehensive Science, 2024)
Based on Law no. 3 of 2020 article 140 concerning Mineral and Coal Mining which states that "Every holder of a Mining Business Permit (IUP) and Special Mining Business Permit (IUPK) is required to submit a reclamation plan and post-mining plan when applying for a Production Operation IUP or Production Operation IUPK as basis for placing reclamation guarantees. The aim of this research is to calculate the direct and indirect costs required for PT Bukit Asam's reclamation plan. The research method used in this research is using activities in the form of visits and direct observations in the field and also collecting articles as support. Direct costs include recountouring costs, revegetation costs and maintenance costs, which are planned at Rp. 12,889,010,229. Meanwhile for indirect costs, the amount is determined from the indirect cost graph, the plan is Rp. 3,054,695,424, so the total cost of the reclamation plan for the West Banko Pit is Rp. 15,943. ,705,653 with an escalation calculation of 5.51%, it becomes IDR 19,758,945,354.